VOLUME POHON BERDIRI PETAK 3a, RPH SALAM. BKPH LAWU UTARA. KPH LAWU DS - Sulistiono, Aris; Rohmatiah, Ahadiati (JURNAL AGRI-TEK, 2016)
Wood is still an important product in forest management activities, therefore the tree volume estimation, measurement of the dimensions of the tree must be done carefully in order to obtain an accurate estimate of the volume of trees that are approaching the estimated volume of the actual volume value. Quality allegations tree volume depends on several factors, including: the level of accuracy desired, tree characteristics, measurement methods, tools used, the current state of the tree dimensional measurement and volume equation used. Estimation of the volume of standing trees research is done in pine plantations (Pinus Jung et de Vriese), in plot 3 a RPH Salam, BKPH North Lawu, KPH Lawu DS, Class VIII KU Forest planting year 1971. Selection of forest class (KU) VIII in this study caused the average grade woods RPH Salam entry into VIII KU and KU logging targets became possible when the time has been unproductive in producing. sap. From the research, the calculation of total sample volume manually tree stand at 171.92 m3 or an average of 2,097 m3 / tree with a minimum volume of 0562 m3 and a maximum of 6.773 m3. Based on the criteria of R2, RSS and SE then elected volume prediction model is Model quadratic equation Y = -1.157 + 2.606 + 15.056 dbh dbh2 .. R2 = 0.996, RSS = 0.1078, SEE = 0107. In calculating the volume using quadratic models shows that the total volume of 82 samples obtained tree volume amounted to 171.87 m3 models or an average of 2,096 m3 / tree. The minimum volume of 0,550 m3 and a maximum of 6.473 m3. Based on t test. test found that t value of 0.053 while t table at 82-1 df = 81 5% (α = 0.05) of 1.615, t (<) is smaller than t table so there is no difference sigifikan / evident between calculations manual volume with the volume calculation using a quadratic models.Keywords: Tree volume, dbh, tree height, form factor, taper function, importance sampling, centroid sampling.